Mystery shopping − the tool of employee communication skills evaluation - Jankal, Radoslav; Jankalová, Miriam (Business: Theory and Practice, 2011)
Mystery shopping is a tool often used for evaluation of providing services quality. It is also a tool, which enables to examine and evaluate communication skills of employees in order to identify their weakness and define the way of improvement. The reason is that their applied abilities are connected with customer´s total perception of providing services. National post operators must learn to listen to their customers through their employees. This process is crucial for the market environment – it enables to gain customer´s loyalty and trust. In order to ensure higher level of customer oriented behaviour between the employees, Slovak Post starts a pilot project called “Mystery Customer”. Main goal of the project is to analyze behavior of selected post office personnel towards the mystery customer. The paper also deals with the practical use of mystery shopping in conditions of Slovak Post.